(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Financial Inclusion is an Important for economic growth and development of Rural Areas. Benefits of development in most of the developing countries are shared of the society which is a small percentage of total population. Financial inclusion is that stair through which, it is possible over a period of time to transform economically deprived people into a large section of society that actively contributes to the economic development of their country. In this study the growth of various schemes has been studied which being launched for the development of the society in the state of Haryana. These schemes helped poor section of the society to get in touch with banking sector regularly.